A retrospective study on femicides assessed at the Institute of Legal Medicine of Milan. Are older women at risk?. (August 2021) - Vignali, Giulia; Franceschetti, Lorenzo; Merzagora, Isabella
Highlights: Femicide is the most serious type of violence against women. Few studies address the theme of temporal trend of the phenomenon and risk factors. The average age increased among victims over the considered 15-years-period. Observed nationality did not reflect the number of foreigners in Italy in proportion. Identified risk factors proved the relevance of anti-violence preventive measures. Abstract: The purpose of the present research is to analyze temporal tend, victim's and perpetrator's specific features and the role of risk factors of femicides assessed at the Institute of Legal Medicine of Milan (in the North of Italy) from 2006 to 2020. The classical definition of femicide (the killing of a woman because of her gender) was used, in order to exclude murders of a woman because of economic issues, neighborhood quarrels, vengeance for previous discussions and other motives. Data were obtained from autopsies findings, local papers and victim relatives' interviews. The analysis of 86 femicides occurred in the judicial district of the Cities of Milan and Monza from 2006 to 2020 were performed. The results show the temporal distribution of the phenomenon, the methods of murders, the mean age of the victims, victims and perpetrators' relationship and nationality, risk factors. Although a reduction in the total number of femicides was observed, the percentage of femicides when compared to the total number of homicides was the same. Also, an increasing mean age of the victims over the period emerged. Moreover, the analysis of nationality of the victims and the perpetrators did not reflect foreign citizens distribution in Italy.